Faktor yang Memengaruhi Tingkat Kelulusan Wawancara Kerja Siswa Bahasa Jepang di LPK Wilayah Makassar dan Sekitarnya - Kasmawati, Kasmawati; Imelda, Imelda (KIRYOKU, 2024)
Japan's increasing need for foreign workers who have international standard Japanese language competencies such as Advanced Basic Japanese Language Level has made 9 Employment Institutions (Sending Organisers and Non-Sending Organisers) compete to have the expected outputs by the Regulations of the Ministry of Manpower and the requirements of Japanese state stakeholders. The method used is a descriptive qualitative combined research method. The data collection techniques used are observation, interviews, and literature studies. The results of this study are to find out the factors that affect the graduation of LPK students in internship interviews or Japanese, including (1) discipline attitude in time; (2) physical, mental, and age abilities; (3) N4 standard certification, 5) Japanese communication skills N4 or higher; (6) a strong internet signal during the interview. The interview process depends on the receiving company. In addition, these nine LPKs provide additional training to participants to practice introducing themselves completely, providing a grid of questions that often arise during interviews such as activities related to work, hobbies, family conditions, and the work of fathers, mothers, and brothers, reasons for working in Japan, reasons for working in the field in Japanese, basic knowledge about the job. LPK also provides Japanese language training and behaves in interviews. With these guidelines, LPK students can undergo job interviews with Japanese companies with good preparation.